Peranan Badan Narkotika Nasional Provinsi Kepri (BNNP) dalam Penegakan Hukum terhadap Pelaku Penyalahgunaan Narkotika di Kepulauan Riau - Rizky Ramadhani; Muhammad Fajar Hidayat (Lembaga Pengembangan Kinerja Dosen, 2024)
This legal study aims to describe and study the problem about the the role of National Narcotics Agency (BNN) in enforcing the law against the perpetrators of the abuse of narcotics for himself (users) in Indonesia. This research is a normative law descriptive qualitative approach. This research uses primary and secondary data. Data collection techniques used by way of literature study. Data analysis techniques used in the writing of this law is qualitative. These results indicate the role of National Narcotics Agency (BNN) in enforcing the law against the perpetrators of the crime of drug abuse in terms of Act No. 35 of 2009 on Narcotics.